SHREC 2020: Classification in cryo-electron tomograms. (October 2020) - Gubins, Ilja; Chaillet, Marten L.; van der Schot, Gijs; Veltkamp, Remco C.; Förster, Friedrich; Hao, Yu; Wan, Xiaohua; Cui, Xuefeng; Zhang, Fa; Moebel, Emmanuel; Wang, Xiao; Kihara, Daisuke; et al.
Highlights: Publicly available, fully-annotated simulated cryo-electron tomogram dataset. Benchmark of six learning-based methods against template matching baseline. Strong correlation between localization/classification performance and molecular weight. Graphical abstract: Abstract: Cryo-electron tomography (cryo-ET) is an imaging technique that allows us to three-dimensionally visualize both the structural details of macro-molecular assemblies under near-native conditions and its cellular context. Electrons strongly interact with biological samples, limiting electron dose. The latter limits the signal-to-noise ratio and hence resolution of an individual tomogram to about 50 (5 nm). Biological molecules can be obtained by averaging volumes, each depicting copies of the molecule, allowing for resolutions beyond 4 (0.4 nm). To this end, the ability to localize and classify components is crucial, but challenging due to the low signal-to-noise ratio. Computational innovation is key to mine biological information from cryo-electron tomography. To promote such innovation, we provide a novel simulated dataset to benchmark different methods of localization and classification of biological macromolecules in cryo-electron tomograms. Our publicly available dataset contains ten tomographic reconstructions of simulated cell-like volumes. Each volume contains twelve different types of complexes, varying in size, function and structure. In this paper, we have evaluated seven different methods of finding and classifying proteins. Six research groups present results obtained with learning-based methods and trained on the simulated dataset, as well as a baseline template matching, a traditional method widely used in cryo-ET research. We find that method performance correlates with particle size, especially noticeable for template matching which performance degrades rapidly as the size decreases. We learn that neural networks can achieve significantly better localization and classification performance, in particular convolutional networks with focus on high-resolution details such as those based on U-Net architecture.